Gaya Kepemimpinan Yang Efekti Dalam Meningkatkan Kinerja Perawat Untuk Keselamatan Pasien - Junimiserya Zalukhu; Nikita G.C Sembiring; Margareth O. Tampubolon; Anggita S. Siregar; Rika Endah Nurhidayah (PENA NURSING, 2023)
Background : Patient safety is the patient's right, the patient has the right to remain safe while in hospital. Patient safety is a priority for healthcare worldwide. One of the factors to improve patient safety is leadership. The purpose: of this study is to provide an overview of effective leadership styles to improve patient safety. Leadership style is one of the external factors that influence the performance of nurses in ensuring patient safety. Transformational leadership has effectiveness in improving nurse performance so that it can have a positive impact on the development of the quality of health services in hospitals.. Methods: This study was descriptive using a convenience sample of 30 respondents with a total sampling technique. Results : a literature study on effective leadership styles to improve patient safety. Research shows this effective leadership style to improve patient safety is the transformational leadership style.